Research Progress on Responsiveness of Activities of Daily Living Scales of Patients with Stroke - XUE Kaiwen; LIU Xiangxiang; ZHANG Zeyu; WANG Yulong (康复学报)
Stroke is characterized with high morbidity, high disability rate and high mortality rate. Motor dysfunction after stroke often leads to decreased activities of daily living (ADL) and affects the quality of life of patients. It is of great significance to select a scale with good responsiveness in clinical and scientific work to reflect the changes of ADL abilities of patients sensitively. In this paper, we summarized the assessment items, characteristics and target population of the Barthel index (BI), functional independence measure (FIM) and modified Rankin scale (mRS), which were commonly used at home and abroad for ADL evaluation of stroke patients, and analyzed the responsiveness of these three scales in stroke patients at different stages of disease. For acute stroke patients, the responsiveness of BI and mRS scale was lower than that of FIM scale. For subacute stroke patients, BI, FIM and mRS Scales all showed good responsiveness, but due to the simple evaluation content, BI scale had a "ceiling" effect and its responsiveness was lower than mRS scale. For patients in chronic stage of stroke, their physical function recovery has almost reached a plateau, and their ADL ability recovery mainly focuses on family and social life, but BI, FIM and mRS scale lack evaluation items about family and social life, resulting in poor responsiveness. Frenchay activities index (FAI) and Longshi Scale (LS) have added IADL evaluation content to the commonly used ADL scales. However, the FAI and LS scales are not widely used, and there is still a lack of relevant studies on their responsiveness. In the future studies, the application of FAI and LS scales in patients with different stages after stroke will be strengthened, and the study on their responsiveness will be carried out, in order to provide a stronger basis for the development of rehabilitation training plan and evaluation of training effect for patients with stroke.